MHD heat transfer in two-layered flow of conducting fluids through a channel bounded by two parallel porous plates in a rotating system - Linga Raju, Temburu; Neela Rao, B. (Zielona Góra: Uniwersytet Zielonogórski)
The paper aims to analyze the heat transfer aspects of a two-layered fluid flow in a horizontal channel under the action of an applied magnetic and electric fields, when the whole system is rotated about an axis perpendicular to the flow. The flow is driven by a common constant pressure gradient in the channel bounded by two parallel porous insulating plates, one being stationary and the other one oscillatory.
Keywords: MHD; two-layered fluids/immiscible fluids; unsteady flow; heat transfer; rigid rotation; porous boundaries